Nature as Theological Witness: An Intertextual Exegesis of Ecological Theology in Fadwā Ṭūqān’s Resistant Poetry - Liza, Fitri; Luhuringbudi, Teguh; Ahmad, Humaira; Abdulghani, Naser Ali; Aimah, Siti (Langkawi: Journal of The Association for Arabic and English, 2026)
While existing scholarship on Fadwā Ṭūqān has extensively examined nationalist and feminist discourses, limited attention has been paid to the ecological dimensions inherent in her resistant poetry. This study investigates the potential of resistant poetry as a medium for articulating ecological theology through an integrated framework combining ecotheology, intertextuality, and green hermeneutics. Employing a qualitative hermeneutic design, the research conducts a close reading of two poems, Shaʿlah al-Ḥarb and Ḥilm al-Dhikrā, utilizing a four-stage analytical procedure: identifying ecological imagery, mapping intertextual symbolic patterns, interpreting theological meaning, and contextualizing resistance discourse. Analysis demonstrates that intertextual mapping reconfigures natural imagery from mere political metaphor to active theological witnesses (āyāt) that respond to environmental degradation. The poetic structure of al-intiqāl al-fannī (artistic transition) operates as a form of ecological daʿwah (moral-environmental call), while the concept of waḥy (divine manifestation) is reinterpreted to frame nature as a site of theological revelation. The study concludes that ecological theology in Arabic resistance literature constitutes an authentic manifestation of al-ʿamal al-īmānī (faith-based ethical action) against systematic environmental injustice. Its contribution lies in developing an interdisciplinary methodology that bridges theological, literary, and environmental perspectives, positioning Arabic resistant poetry as a theological maʿrūf (recognized moral discourse) within global environmental humanities.